(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
Metaphor is an effective way of forming medical terms. Metaphors are also very useful in creating medical terms. In the article, the medical terms formed on the basis of metaphor are grouped based on their dictionary meanings.